Gender discrimination in the employment of secretaries in the Nigerian labour market - Olapade, Bolanle Ibijoke (Journal of Professional Secretaries and Office Administrators, 2015)
There are different types of secretaries whether male or female.Personal Secretary usually abbreviated as PA is a personal secretary by academic or year of service and qualifications which might not include office technology experience. His own work is just to advise the boss and at the same time need the assistant of professional secretary to bring his/her work to perfection. Therefore, professional secretary is inevitable in the Nigerian labour market.